Kualitas Benih dan Pertumbuhan Kedelai yang Berasal dari Jenis Tanah dan Sistem Pertanaman Berbeda - Permanasari, Indah; Septirosya, Tiara; Hera, Novita (Universitas Bangka Belitung, 2024)
Soybean is one of the national strategic commodities. The increasing of soybeans needs, it is necessary to prepare the high quality seed. Different environmental conditions such as soil condition and cropping system will affect the quality of seed. The aimed of this study was to investigates the quality of soybean seed from different types of soil and cropping system. The research was conducted experimentally using Randomized Block Design (RBD) with two factors. The first factor is the source of seeds that come from two types of soil, namely peat and mineral. The second factor is seeds that come from monoculture and intercropping. Based on the results of the study, it showed that the fat and protein content of soybean seeds from seeds planted on mineral soils was better than seeds from peat soils. Planting soybean seeds in peat soil can increase the fiber and carbohydrate content of the seeds as well as the viability and vigor of the seeds. Intercropping system increased protein and fiber content of seed, but not affect its vegetative growth.